Difficulties Faced by Iraqi University Students of English in Writing Composition from the Students' Point of View - حسين يحيى, داليا (Al-Adab Journal, 2018)
The majority of EFL students face difficulties in writing composition which reflect negatively on their exam results. The researcher has noticed this problem and decided to trace the difficulties they face in order to put an end to them or at least to minimize them. To fulfill the aim of the research, a sample of (100) second year students of English Department / College of Basic Education / Diyala University have been selected as the subjects of this research. A scaled questionnaire as an instrument of measurement is used in this research to be an investigatory tool. The results of this research proves that the hypothesis of this study is verified and accepted which reads that Iraqi students of English face challenges in writing composition. Then, the conclusion have been made on the basis of the findings, and the recommendations have been drawn.